A Case of Ruptured Aneurysm of the Persistent Sciatic Artery Presenting Acute Lower Limb Ischemia - Shimizu, Noriyuki (The Editorial Committee of Annals of Vascular Diseases, 2009)
Only 5 cases of ruptured aneurysm of the persistent sciatic artery have been previously reported to date. We experienced a case of ruptured aneurysm of the persistent sciatic artery presenting acute lower limb ischemia. Physical examination showed a pulsatile mass with a subcutaneous hemorrhage in the left buttock, drop foot and paresthesia of the foot due to limb ischemia. An enhanced computed tomography scan showed a ruptured aneurysm of the left persistent sciatic artery at the level of the greater trochanter. An exclusion of the aneurysm and creation of common iliac to popliteal artery bypass was performed as an emergency operation.